The Cambridge companion to world crime fiction - Gulddal, Jesper ca. 20./21. Jh; King, Stewart 1968-; Rolls, Alistair 1971- (Cambridge University Press, 2022)
What is world crime fiction? / Jesper Gulddal & Stewart King -- Crime fiction and the international publishing industry / Karl Berglund -- The translation and circulation of crime fiction / Susan Bassnett & Brigid Maher -- The international crime fiction collection / Barbara Pezzotti -- Regional crime fiction / Andrew Pepper -- Women in world crime fiction / Nicole Kenley -- East Asian crime fiction / Satoru Saito -- Crime fiction in South Asia / Laura Brueck & Francesca Orsini -- Arab crime fiction / Jonathan Smolin -- The crime fiction of Sub-Saharan Africa / Désiré Nyela -- European crime fiction / Jesper Gulddal & Stewart King -- Scandinavian crime fiction / Jakob Stougaard-Nielsen -- Iberian and Latin American crime fiction / Glen S. Close & Elena Losada Soler -- World crime fiction in French / Jarrod Hayes & Alistair Rolls
Keywords: Kriminalroman; Detective and mystery stories / History and criticism; Aufsatzsammlung